Forgotten healers women and the pursuit of health in Late Renaissance Italy - Strocchia, Sharon T., 1951- (I Tatti studies in Italian Renaissance history., 2019)
In Renaissance Italy women played a more central role in providing health care than historians have thus far acknowledged. Women from all walks of life--from household caregivers and nurses to nuns working as apothecaries--drove the Italian medical economy. In convent pharmacies, pox hospitals, girls' shelters, and homes, women were practitioners and purveyors of knowledge about health and healing, making significant contributions to early modern medicine. Sharon Strocchia offers a wealth of new evidence about how illness was diagnosed and treated, whether by noblewomen living at court or poor nurses living in hospitals. She finds that women expanded on their roles as health care providers by participating in empirical work and the development of scientific knowledge. Nuns, in particular, were among the most prominent manufacturers and vendors of pharmaceutical products. Their experiments with materials and techniques added greatly to the era's understanding of medical care. Thanks to their excellence in medicine urban Italian women had greater access to commerce than perhaps any other women in Europe. Forgotten Healers provides a more accurate picture of the pursuit of health in Renaissance Italy. More broadly, by emphasizing that the frontlines of medical care are often found in the household and other spaces thought of as female, Strocchia encourages us to rethink the history of medicine.--